Factors associated with hospital participation in Centers for Medicare and Medicaid Services' Accountable Care Organization programs. Issue 2 (April 2019) - Chukmaitov, Askar S.; Harless, David W.; Bazzoli, Gloria J.; Deng, Yangyang
Abstract : Background: In 2012, the Centers for Medicare and Medicaid Services (CMS) initiated the Medicare Shared Savings Program (MSSP) and Pioneer Accountable Care Organization (ACO) programs. Organizations in the MSSP model shared cost savings they generated with CMS, and those in the Pioneer program shared both savings and losses. It is largely unknown what hospital and environmental characteristics are associated with the development of CMS ACOs with one- or two-sided risk models. Purpose: The aim of this study was to assess the organizational and environmental characteristics associated with hospital participation in the MSSP and Pioneer ACOs. Methodology: Hospitals participating in CMS ACO programs were identified using primary and secondary data. The ACO hospital sample was linked with the American Hospital Association, Health Information and Management System Society, and other data sets. Multinomial probit models were estimated that distinguished organizational and environmental factors associated with hospital participation in the MSSP and Pioneer ACOs. Results: Hospital participation in both CMS ACO programs was associated with prior experience with risk-based payments and care management programs, advanced health information technology, and location in higher-income and more competitive areas. Whereas various health system types were associated with hospital participation in the MSSP, centralized health systems, higher numbers of physicians in tightly integrated physician–organizational arrangements, and location in areas with greater supply of primary care physicians were associated with Pioneer ACOs. Favorable hospital characteristics were, in the aggregate, more important than favorable environmental factors for MSSP participation. Conclusion: MSSP ACOs may look for broader organizational capabilities from participating hospitals that may be reflective of a wide range of providers participating in diverse markets. Pioneer ACOs may rely on specific hospital and environmental characteristics to achieve quality and spending targets set for two-sided contracts. Practice Implications: Hospital and ACO leaders can use our results to identify hospitals with certain characteristics favorable to their participation in either one- or two-sided ACOs.